A 1-year cross-sectional study on the predominance of infuenza among hospitalized children in a tropical area, Kota Kinabalu, Sabah - Kai, Joo Lim; Jecelyn Leaslie John; Syed Sharizman Syed Abdul Rahim; Richard Avoi; Mohd Rohaizat Hassan; Mohammad Saffree Jeffree; Mohd Yusof Ibrahim; Kamruddin Ahmed (BioMed Central Ltd., 2022)
Background: Children are at higher risk of infuenza virus infection, and it is difficult to diagnose. They are also responsible for the transmission of infuenza because of their longer viral shedding compared to adults. In Malaysia, studies on infuenza in children are scarce, and as a result, policy decisions cannot be formulated to control the infection. Hence, the objective of this study is to determine the prevalence and epidemiological characteristics of infuenza among children with upper respiratory symptoms in the Sabah state of Malaysia. Methods: A cross-sectional study with a simple random sampling was conducted among children with upper respiratory symptoms in Sabah from 1 March 2019 to 29 February 2020. Patients admitted to a pediatric ward of Sabah Women and Children’s Hospital who presented with a fever >38 °C and cough within 48 h of admission were enrolled in this study. A nasopharyngeal swab was taken, and infuenza was diagnosed by lateral flow test. Clinical features of infuenza-positive children were compared with children whose results were negative. Results: A total of 323 nasopharyngeal samples were collected, and 66 (20.4%) of them were positive for infuenza. Fifty-six (85%) were infected by infuenza A whereas ten (15%) were by infuenza B virus. Higher temperature (aOR 2.03, 95% CI 1.296–3.181), less activity (aOR 2.07, 95% CI 1.158–3.693), and seizure (aOR 4.2, 95% CI 1.614–10.978) on admission were significant risk factors associated with infuenza in children. Meteorology parameters such as humidity and rainfall amount were statistically significant at 95% CI [1.133 (1.024–1.255)] and 95% CI [0.946 (0.907–0.986)]. Conclusion: The prevalence of infuenza was high among children with upper respiratory symptoms, and they were infected predominantly with the infuenza A virus. Children presented with seizures, less activity, and fever were the significant risk factors for infuenza. Infuenza vaccination should be prioritized as preventive measures for children.